2013
DOI: 10.4172/2157-7617.1000130
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impacts of Climate Change on Artisanal Fisheries of Nigeria

Abstract: Artisanal fisheries contribute to sustainable livelihoods of people in several ways accounting for more than 80% of total fish production in Nigeria. Climate change arising from global warming, increasing temperature, stratification and changes in ecosystem processes brings flooding, precipitation, evaporation, run-off and flow with potential serious negative impacts on fish assemblages and productions, fishing activities, fishers catch per unit effort, fish breeding, morphology, resistance to species invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Fish has been reported to be a good source of food and means of livelihood to many African populace [1]. However, this industry is constrained by availability of alternative nutritive protein source as replacement for fish meal [2,3] Naylor et al Several studies conducted have revealed the use of some plant protein sources like Moringa leaf meal, Soybean meal and so on as fish meal replacement in fish diets [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Fish has been reported to be a good source of food and means of livelihood to many African populace [1]. However, this industry is constrained by availability of alternative nutritive protein source as replacement for fish meal [2,3] Naylor et al Several studies conducted have revealed the use of some plant protein sources like Moringa leaf meal, Soybean meal and so on as fish meal replacement in fish diets [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%